THE EFFECT OF N-ACETYL CYSTEINE TO SPERM MOTILITY, VIABILITY, AND CONCENTRATION OF SPRAGUE DAWLEY RATS WITH NICOTINE INHALATION EXPOSURE - Waskito, Dwi; Renaldo, Johan; Soebadi, Doddy M (Indonesian Urological Association, 2019)
Objective: To prove and analyze the difference of sperm motility, viability, and concentration of Sprague Dawley rats which were exposed to nicotine inhalation, with rats treated with N-acetyl cysteine (NAC) orally and exposed to nicotine inhalation. Material & Methods: Twenty seven rats were allocated into three group. Control group (C) (aquadest inhalation 1 mL/kgBW/day), treatment group 1 (N) (nicotine inhalation 1 mg/kgBW/day), and treatment group 2 (N-NAC) (nicotine inhalation 1 mg/kgBW/day and oral NAC administration 150 mg/kgBW/day), with all treatment were given for 30 days. Orchidectomy was performed on day 31 to collect semen sample for sperm analysis (motility, viability, and concentration). Results: There was a significant decrease in all parameters from N group compared to C group. Significant increase were found in sperm motility and viability parameters in the N-NAC treatment group compared to N group. While the sperm concentration parameters of the N-NAC group had a non-significant increase compared to N group. Conclusion: Exposure to nicotine inhalation decreased sperm motility, viability, and concentration of Sprague Dawley strain rats, and NAC had a protective effect on sperm of rats which was exposed to nicotine inhalation.